Expeditious Pump Rescheduling in Multisource Water Distribution Networks. (2015) - Scarpa, F.; Lobba, A.; Becciu, G.
Abstract: Cost minimization is the main issue for water companies when establishing pumping regimes for water distribution. Remarkable reductions in operation costs can be achieved by optimizing the pump scheduling problem. In this paper a near optimum solution is proposed for internal multi-sources networks with a large amount of pumps per station. The proposed method is based on a local search algorithm which explores the neighborhood of an optimized solution obtained by the subdivision of the network into pumping station influence areas.A real case of study is presented and discussed, results are also compared to the solution obtained with a GA.